2016
DOI: 10.5897/ajmr2015.7534
|View full text |Cite
|
Sign up to set email alerts
|

Insights of maize lethal necrotic disease: A major constraint to maize production in East Africa

Abstract: Maize Lethal Necrotic Disease (MLND) is a new disease in East Africa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Notably, there were viruses that were detected in some areas that had shown no disease incidence by visual observation. Symptoms caused by MLN viruses can also differ based on the age of the maize plant, the variety implicated, environmental factors, MCMV and SCMV virus strain, and various viruses may induce similar symptoms in the same plant (Kiruwa et al, 2016;Mezzalama, 2015;Wang et al, 2017). The study found that symptoms of the disease were seen in some cases during the study, even though there was no MCMV or SCMV.…”
Section: Figure 11 Mln Incidence On Commonly Grown Maize Varieties Over the Yearsmentioning
confidence: 84%
“…Notably, there were viruses that were detected in some areas that had shown no disease incidence by visual observation. Symptoms caused by MLN viruses can also differ based on the age of the maize plant, the variety implicated, environmental factors, MCMV and SCMV virus strain, and various viruses may induce similar symptoms in the same plant (Kiruwa et al, 2016;Mezzalama, 2015;Wang et al, 2017). The study found that symptoms of the disease were seen in some cases during the study, even though there was no MCMV or SCMV.…”
Section: Figure 11 Mln Incidence On Commonly Grown Maize Varieties Over the Yearsmentioning
confidence: 84%
“…Given the severe losses it has caused since 2011 in mixed infection with the potyvirus SCMV in East Africa [7, 63, 64], China [10, 65, 66] and Ecuador [13], and given the cost of screening seed worldwide to ensure absence of this seed-transmitted virus [63, 67, 68], MCMV is almost certainly the most economically important virus in the >76-member Tombusviridae family. Thus, it is imperative to understand the life cycle of MCMV, including translation, to identify molecular targets for genetic approaches to control this virus.…”
Section: Discussionmentioning
confidence: 99%
“…Given the severe losses it has caused since 2011 in mixed infection with the potyvirus SCMV in East Africa (7,63,64), China (10,65,66) and Ecuador (13), and given the cost of screening seed to ensure absence of this seed-transmitted virus (63,67,68), MCMV is almost certainly the most economically important virus in the >76-member Tombusviridae family (23).Thus, it is imperative to understand the life cycle of MCMV, including translation, to identify molecular targets for genetic approaches to control this virus. All tombusvirids that have been studied contain a 3' CITE (35,40,60,69,70), yet these are not predictable because the class of 3' CITE a tombusvirid possesses does not always correlate with phylogeny (35,52).…”
Section: Cap-independent Translation Of MCMV Rnamentioning
confidence: 99%